Hydrology study and trend of rainfall event at UMP Gambang - Muhammad Amirudin, Shikh Ali (2015)
This research describes experimental studies on the collected data in order to identify the different between rainfall data collect by using rain gauge and weather station. The collected data also can be used for research and planning our daily activities. The location weather station and rain gauge existed in Kolej Kediaman 2, Universiti Malaysia Pahang (UMP) Gambang. The data from Department of Irrigation And Drainage (JPS KUANTAN) is used to design rainfall temporal pattern for five years from 2008 to 2014 at four best nearest place hydrological station with station UMP Gambang. The rainfall data collected from a weather station UMP Gambang were used to identify the trend of rainfall event at UMP Gambang and make comparison with data rainfall and wind data collected using weather station. The relationship between relative humidity, temperature and wind speed towards the rainfall pattern was analyzed. Based from the analysis, from October to February total of rainfall will increase with maximum rainfall while start on March until April the total of rainfall start decreased. It shows the changes from wet season to driest season.